Effects of Smartphone-Based Stress Management on Improving Work Engagement Among Nurses in Vietnam: Secondary Analysis of a Three-Arm Randomized Controlled Trial - Sasaki, Natsu (J Med Internet Res, 2021)
BACKGROUND: Work engagement is important for employee well-being and work performance. However, no intervention study has investigated the effect of an eMental Health intervention on work engagement among workers in low- and middle-income countries (LMICs). OBJECTIVE: The aim of the study was to examine the effects of a newly developed smartphone-based stress management program (ABC Stress Management) on improving work engagement among hospital nurses in Vietnam, an LMIC. METHODS: Full-time registered nurses (n=949) were randomly assigned to one of 2 intervention groups or a control group. The intervention groups were a 6-week, 6-lesson program offering basic cognitive behavioral therapy (CBT-based stress management skills), provided in either free-choice (program A) or fixed order (program B). Work engagement was assessed at baseline and 3-month and 7-month follow-ups in each of the 3 groups. RESULTS: The scores of work engagement in both intervention groups improved from baseline to 3-month follow-up, and then decreased at the 7-month follow-up, while the score steadily increased from baseline to 7-month follow-up in the control group. Program B showed a significant intervention effect on improving work engagement at the 3-month follow-up (P=.049) with a small effect size (Cohen d= 0.16; 95% CI 0.001 to 0.43]). Program A showed nonsignificant trend (d=0.13; 95% CI –0.014 to 0.41; P=.07) toward improved engagement at 3 months. Neither program achieved effectiveness at the 7-month follow-up. CONCLUSIONS: The study demonstrated that a fixed order (program B) delivery of a smartphone-based stress management program was effective in improving work engagement in nurses in Vietnam. However, the effect was small and only temporary. Further improvement of this program is required to achieve a greater effect size and more sustained, longer lasting impact on work engagement. TRIAL REGISTRATION: University Hospital Medical Information Network Clinical Trials Registry UMIN000033139; tinyurl.com/55gxo253 INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): RR2-10.1136/bmjopen-2018-025138